Experiencing Personal Data Protection on the Internet and Its Possibilities of Recognition and Enforcement in Ukraine - Melnyk, Petro; Kostenko, Oleksii Volodymirovich; Blinova, Hanna Oleksandrivna; Shynkarenko, Iryna Igorivna (Universidad Hemisferios, 2021)
The purpose of this article is to find the most successful ways, forms and methods of personal data protection on the Internet among foreign countries for domestic political and legal realities. The following methods were used in the article: dialectical, logical-semantic, comparative-legal, documentary analysis, analytical, information-analytical. Issues related to the adaptation of the successful experience of a number of developed countries in the field of personal data protection on the Internet are brought up for discussion. Some options are covered and specified, which include effective methods and ways to implement an effective mechanism for personal data protection on the Internet in Ukraine. It is emphasized that the protection and proper confidentiality of personal data of individuals is one of the key tasks currently facing modern jurists. It is also added that the nature and specifics of the use and protection of personal data of individuals, including on the Internet, are extremely closely related to the institution of intellectual property. Emphasis is placed on the fact that the level of protection of personal data of individuals in a country is an indicator of the extent to which such a state meets the criteria of freedom, democracy, and the rule of law.